THE ROLE OF DEEP BASEMENT DURING CONTINENT-CONTINENT COLLISION: A REVIEW - Ryan P.D. (My University, 2001)
Structural, geophysical and metamorphic studies show that collisional orogeny thickens the crust by a factor of two or more. A large volume of continental material at the base of the orogen is, therefore, subject to eclogite facies conditions. Phase equilibration results in a loss of buoyancy and thermodynamic heating of this crustal root. This dense crustal material may be partially subducted, as in the Alps or the Himalayas, and lost to the system. Alternatively, it may rest isostatically below the Moho until it is partially exhumed during orogenic collapse, as in the Scandinavian Caledonies or the Tonbai-Dabie Mountains. Remnant orogenic roots may exist as seismically reflective mantle and provide a locus for subsequent Wilson Cycle rifting. The rate at which these phase transformation take place may have a profound buffering effect on the amount and duration of orogenic contraction. Isostatically compensated transient 2-dimensional finite element thermal models are presented, which seek to place some limits on these processes. It is interesting to speculate whether more is learnt about the process of orogeny from a single exhumed eclogitic boundin or from mapping nappe complexes.